Digital technologies for health financing in low-income and middle-income countries: a scoping review protocol - Pioch, Carolina; Struckmann, Verena; Brikci, Nouria; De Allegri, Manuela; Emmrich, Julius; Knauss, Samuel; Mathauer, Inke; Opoku, Daniel; Quentin, Wilm (BMJ open, 2024)
Introduction Universal health coverage (UHC) is a global priority, ensuring equitable access to quality healthcare services without financial hardship. Many countries face challenges in progressing towards UHC. Health financing is pivotal for advancing UHC by raising revenues, enabling risk-sharing through pooling of funds and allocating resources. Digital technologies in the healthcare sector offer promising opportunities for health systems. In low-income and middle-income countries (LMICs), digital technologies for health financing (DTHF) have gained traction, supporting these three main functions of health financing for UHC. As existing information on DTHF in LMICs is limited, our scoping review aims to provide a comprehensive overview of DTHF in LMICs. Our objectives include identifying and describing existing DTHF, exploring evaluation approaches, examining their positive and negative effects, and investigating facilitating factors and barriers to implementation at the national level. - Methods and analysis Our scoping review follows the six stages proposed by Arksey and O’Malley, further developed by Levac et al and the Joanna Briggs Institute. The reporting adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews framework. Eligibility criteria for studies reflect the three core elements of the search: (1) health financing, (2) digital technologies and (3) LMICs. We search multiple databases, including Medline via PubMed, EMBASE via Ovid, the Web of Science Core Collection, CENTRAL via Cochrane and the Global Index Medicus by the WHO. The extracted information is synthesised from both quantitative and qualitative studies. - Ethics and dissemination As our scoping review is based solely on information gathered from previously published studies, documents and publicly available scientific literature, ethical clearance is not required for its conduct. The findings are presented and discussed in a peer-reviewed article, as well as shared at conferences relevant to the topic.
Gesehen am 24.02.2025